Sport-specific video-based reative agility training in rugby union players - Engelbrecht, L. (2011)
In rugby union the players are constantly faced with a changing environment and successful play requires the players to correctly interpret and respond to these changing situations. Reactive agility (RA) is an open and complex motor skill that has the ability to distinguish between higher and lesser skilled athletes. Evasive RA manoeuvres are most likely to lead to successful tackle breaks and advancing beyond the advantage line. The current study investigated the effectiveness of a sport-specific video-based RA training program for rugby union players. The video-based training (VT) was compared to field-based training (FT) to determine if it could be a possible alternative method in RA conditioning. Twenty six male rugby union players (aged 18 to 24 years) volunteered to participate in the study. They were divided into forwards and backs and then randomly divided into VT (n = 10), FT (n =9) or control (C) (n =7). Players in VT and FT completed a six week intervention program of two sessions per week. All the players were tested pre and post intervention and six weeks after the completion of the intervention. The tests included anthropometrical measurements (height, body mass, % BF, % LBM), sprint speed, change of direction speed (CODS), RA, anaerobic capacity (repeated sprint) and aerobic endurance (multistage shuttle run). The results showed that sprint speed was not influenced by any of the training interventions (p > 0.05). VT resulted in improvements in CODS and VT performed significantly better than FT (p < 0.05). However, these improvements were not maintained after the intervention period. RA improved significantly in both VT and FT groups (p < 0.05). The improvement in RA was also significantly better than the changes in C (p < 0.05). The training effect was possibly more beneficial in FT than VT to improve RA (3.0 + 4.4%). Following the retention Stellenbosch University period VT and FT only dropped their RA performance slightly (0.8 + 7.7% and 1.2 + 4.6%, respectively), with no clear benefit or disadvantage for any of the training groups. Both VT and FT produced significant improvements in RA performance of intermediate rugby union players, and these changes were significantly greater than with rugby training alone (C). Therefore, VT is an effective alternative conditioning method or add-on to improve RA in rugby union.